Genetic Variance of Metabolomic Features and Their Relationship With Malting Quality Traits in Spring Barley - Guo, Xiangyu; Sarup, Pernille; Jensen, Jens Due; Orabi, Jihad; Kristensen, Nanna Hellum; Mulder, Frans A. A.; Jahoor, Ahmed; Jensen, Just (Frontiers in Plant Science, 2020)
Barley is the most common source for malt to be used in brewing beer and other alcoholic beverages. This involves converting the starch of barley into fermentable sugars a process that involves malting, that is germinating of the grains, and mashing, which is an enzymatic process. Numerous metabolic processes are involved in germination, where distinct and time-dependent alterations at the metabolite levels happen. In this study, 2,628 plots of 565 spring malting barley lines from Nordic Seed A/S were investigated. Phenotypic records were available for six malting quality traits: filtering speed, wort clearness, extract yield, wort color, beta glucan, and wort viscosity. Each line had a set of dense genomic markers. In addition, 24,018 metabolomic features (MFs) were obtained for each sample from nuclear magnetic resonance spectra for wort samples produced from each experimental plot. The genetic variation in the MFs was investigated using a univariate model, and the relationship between MFs and the malting quality traits was studied using a bivariate model. Results showed that a total of 8,604 MFs had heritability estimates significantly larger than 0 and for all malting quality traits, there were genetic correlations with up to 86.77% and phenotypic correlations with up to 90.07% of the significant heritable MFs. In conclusion, around one third of all MFs were significantly heritable, among which a considerable proportion had significant additive genetic and/or phenotypic correlations with the malting quality traits (wort color, wort viscosity and beta glucan) in spring barley. The results from this study indicate that many of the MFs are heritable and MFs have great potential to be used in breeding barley for high malting quality.